Huguenot Networks, 1560–1780 - Larminie, Vivienne, author.
1 online resource (256 pages)
Keywords: These chapters explore how a religious minority not only gained a toehold in countries of exile, but also wove itself into their political, social, and religious fabric. The way for the refugees’ departure from France was prepared through correspondence and the cultivation of commercial, military, scholarly and familial ties. On arrival at their destinations immigrants exploited contacts made by compatriots and co-religionists who had preceded them to find employment. London, a hub for the “Protestant international” from the reign of Elizabeth I, provided openings for tutors and journalists. Huguenot financial skills were at the heart of the early Bank of England; Huguenot reporting disseminated unprecedented information on the workings of the Westminster Parliament; Huguenot networks became entwined with English political factions. Webs of connection were transplanted and reconfigured in Ireland. With their education and international contacts, refugees were indispensable as diplomats to Protestant rulers in northern Europe. They operated monetary transfers across borders and as fund-raisers, helped alleviate the plight of persecuted co-religionists. Meanwhile, French ministers in London attempted to hold together an exceptionally large community of incomers against heresy and the temptations of assimilation. This is a story of refugee networks perpetuated, but also interpenetrated and remade.